2022
DOI: 10.1038/s41467-022-28601-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterotypic interactions drive antibody synergy against a malaria vaccine candidate

Abstract: Understanding mechanisms of antibody synergy is important for vaccine design and antibody cocktail development. Examples of synergy between antibodies are well-documented, but the mechanisms underlying these relationships often remain poorly understood. The leading blood-stage malaria vaccine candidate, CyRPA, is essential for invasion of Plasmodium falciparum into human erythrocytes. Here we present a panel of anti-CyRPA monoclonal antibodies that strongly inhibit parasite growth in in vitro assays. Structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
86
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(92 citation statements)
references
References 61 publications
(87 reference statements)
6
86
0
Order By: Relevance
“…We showed CyRPA to be the target of potent in vitro straintranscending parasite neutralizing antibodies that was substantiated by other groups, thus establishing CyRPA as a promising blood-stage vaccine target (17,18,25). Recent findings from our lab that demonstrated synergistic invasion Recombinant production of CyRPA has been reported using various expression platforms including mammalian (HEK293) (18,(45)(46)(47)(48), bacteria (E. coli) (16, 18) and insect expression system (49,50). We chose bacterial system for CyRPA expression since it has several advantages over the others: 1) ease to operate, 2) costeffective as it allows high expression yields and easy scale-up of the process, 3) time effective due to fast growth kinetics of bacteria (51).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We showed CyRPA to be the target of potent in vitro straintranscending parasite neutralizing antibodies that was substantiated by other groups, thus establishing CyRPA as a promising blood-stage vaccine target (17,18,25). Recent findings from our lab that demonstrated synergistic invasion Recombinant production of CyRPA has been reported using various expression platforms including mammalian (HEK293) (18,(45)(46)(47)(48), bacteria (E. coli) (16, 18) and insect expression system (49,50). We chose bacterial system for CyRPA expression since it has several advantages over the others: 1) ease to operate, 2) costeffective as it allows high expression yields and easy scale-up of the process, 3) time effective due to fast growth kinetics of bacteria (51).…”
Section: Discussionmentioning
confidence: 63%
“…Recombinant production of CyRPA has been reported using various expression platforms including mammalian (HEK293) ( 18 , 45 48 ), bacteria ( E. coli) ( 16 , 18 ) and insect expression system ( 49 , 50 ). We chose bacterial system for CyRPA expression since it has several advantages over the others: 1) ease to operate, 2) cost-effective as it allows high expression yields and easy scale-up of the process, 3) time effective due to fast growth kinetics of bacteria ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, if we are proposing that the community uses these antibodies to harmonise and standardise assays, it is important that we understand the effects of post-translational modifications on the material and ensure we are using a defined and optimised production process. Indeed, work by our group and others ( Ragotte et al., 2022 ) has already shown that the choice of cell expression system used in the production of the antibodies effects antibody activity and we currently are investigating this in more detail at NIBSC. Furthermore, it is known that post-translational modifications are important for the activity of biological molecules including glycosylation in the context of immunoglobulins ( Schroeder and Cavacini, 2010 ; Subedi and Barb, 2015 ; van de Bovenkamp et al., 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…Combining mAbs against different antigens has the potential to increase transmission-blocking activity, as does combining mAbs against different epitopes of the same antigen, which can increase activity through heterotypic interactions ( Ragotte et al., 2022 ). Combining mAbs against different epitopes of Pfs230 D1 or Pfs230 D1 and Pfs48/45 significantly increased transmission-blocking activity ( Singh et al., 2020 ), warranting further investigation of different mAb combinations.…”
Section: Discussionmentioning
confidence: 99%
“…The epitopes displayed by immunogens should be carefully considered; displaying multiple antigens can elicit antibodies that work synergistically but eliciting a wide polyclonal response can elicit antagonistic antibodies that reduce transmission-blocking activity ( Alanine et al., 2019 ; Ragotte et al., 2022 ). In addition, synergistic effects appear to be dependent on antigen combination; vaccination with both Pfs230 and Pfs25 was found to elicit antibody responses no higher than those elicited by each antigen individually ( Menon et al., 2017 ; Healy et al., 2021 ) and combinations of anti-Pfs230 and -Pfs25 mAbs did not show increased transmission-blocking activity ( Singh et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%